Catchment area assessment and socio-economic consequences for agricultural sustainability in the Himalayan region - JAISWAL, SHATRUHAN; THAKUR, ROOP CHAND (Journal of Soil and Water Conservation, 2025)
In the Himalayan region glaciers and annual snowfalls feed rivers serving 47% of the world’s population. There is no other region in what is happening with a same population, rainfall shortage, reliance on agriculture, allure of mega-project locations, and susceptibility to climate change. Being a part of the north-western Himalayan region, block has 31632 ha area owned by the farmers on which various horticultural, agricultural including vegetable cultivation and animal husbandry activities are carried out. The status of these activities as revealed by the survey is summarized that the predominant fruit crops comprised of apple, plum, pear, pomegranate, pecnut, apricot, almond, persimmon and walnut. Apple accounted for 51.4% area among the fruit crops. Rest of the area was covered by other fruit crops. About 51.9% farmers are growing improved varieties of apple. 3.4% farmers are irrigating their fruit crops. 61.0% of the farmers apply FYM. The block has 15748 hectare area on which various cereal and vegetable crops are grown. Among the cereal crops, maize dominates during Kharif season whereas wheat and barley are the main crops during Rabi season. Rajmash and Urd are also grown during the kharif season. The most preferred vegetable crops are tomato, peas, garlic, cauliflower, potato and cabbage. The main objective of this study was to conduct a socio-economic study and assess the extent of horticultural, agricultural, vegetable production, and animal husbandry development across Community Development Blocks through field surveys by NERIL. Keeping in view from the complete analysis done so far the following recommendation may be made of an additional area may be brought under irrigation as well as from the area under field crops, efforts may be made to bring some area under fruit crops. Senile orchards may be rejuvenated and leguminous grasses like white clover or red clover may be grown in between so as to improve the fodder quality as well as add nitrogen to the orchard soils. Where ever agriculture is done on sloppy lands, bench terracing should be done and Water harvesting structures may be raised simultaneously some cultivated area be put under fodder cultivation. A financial outlay of Rs.3099.63 is recommended to implement these recommendations in bare minimum of 1% area owned by the farmers in the entire catchment.